2D Geoelectric Imaging of the Uneme-Nekhua Fracture Zone. (4th June 2014) - Aminu, Muslim B.; Akande, Tunde M.; Ishola, Olubukola A.
Abstract : We have employed 2D geoelectric imaging to reveal the geometry and nature of a fracture zone in Uneme-Nekhua, southwestern Nigeria. The fracture zone is discernable from an outcropping rock scarp and appears to define the course of a seasonal stream. Data were acquired using the dipole-dipole survey array configuration with electrode separation of 6 m and a maximum dipole length of 60 m. Three traverses with lengths varying between 72 m and 120 m were laid orthogonal to the course of the seasonal stream. 2D geoelectric images of the subsurface along the profiles imaged a north-south trending fracture zone. This fracture zone appears to consist of two vertical fractures with more intense definition downstream. The eastern fracture is buried by recent sediment, while the western fracture appears to have experienced more recent tectonic activity as it appears to penetrate through the near surface. Perhaps at some point, deformation ceased on the eastern fracture and further strain was transferred to the western fracture. The fracture zone generally defines the course of the north-south seasonal stream with the exception of the downstream end where the fracture appears to have died out entirely. Two associated basement trenches lying parallel to and east of the fracture zone are also imaged.